Survival and growth rates of Sutchi catfish (Pangasianodon hypophthalmus) juveniles under different light wavelengths and intensities - Nor Amira Yusoff,; Muhammad Firdaus Sallehudin,; Tan, Nai Han; Normawaty Mohammad Noor,; Yukinori Mukai, (Malaysian Society of Applied Biology, 2016)
This study report the effects of light intensity on the optimum light wavelength and intensity on the survival rate, specific growth rate, and production index of sutchi catfish (Pangasianodon hypophthalmus, Sauvage, 1878) juveniles. The sutchi catfish juveniles (69 days old) with average initial body length of 5.14 cm and body weight of 1.11 g were reared for 11 days (20 individuals/30 L) under five light wavelengths (white with λmax 446 and 566 nm, blue 454 nm, green 520 nm, yellow 590 nm, and red 632 nm) with three light intensities (1.40×10-3, 1.40×10-2 and 1.40 μmol/m²/s) in triplicates. A twoway ANOVA analysis showed that light intensities had significantly (P < 0.05) affected the survival and specific growth rates of sutchi catfish juveniles. A Bonferroni post hoc analysis showed that the survival and specific growth rates were significantly high (P < 0.05) under the light intensity of 1.40 μmol/m²/s. In addition, there was a tendency of high growth rate, specific growth rate and production index under red light. Thus, the light intensity of 1.40 μmol/m²/s under red light is recommended for the rearing of sutchi catfish juveniles for better survival rate, growth rate and production index.